Implementation of Restaurant Business Standards Policy to Improve Service Quality in Event Organizations (Banquets) - Wim Johannes Winowatan (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
This study examines the implementation of the Ministry of Tourism and Creative Economy Regulation No. 4 of 2021 concerning Restaurant Business Standards for event (banquet) hosting in Parepare City. The background of this research is the importance of improving restaurant service quality to support the tourism sector, particularly Meetings, Incentives, Conferences, and Exhibitions (MICE) activities.This study uses a qualitative approach to gain an in-depth understanding of the phenomena observed in the field, particularly regarding the implementation of Minister of Tourism and Creative Economy Regulation No. 4 of 2021 concerning restaurant business standards in the context of providing banquet service delivery in Parepare City. The research method also uses a qualitative approach through interviews, observation, and document analysis. The results show that policy implementation is still suboptimal, characterized by minimal understanding among business actors, limited certified workforce, inadequate facilities, and weak oversight from local governments. This study concludes that there is a gap between national policy standards and operational practices in the field. Strengthening strategies are needed in the form of regulatory socialization, HR training and certification, business incentives, and more consistent supervision to improve the quality of banquet services in Parepare City and support the sustainable competitiveness of regional tourism.